2003
DOI: 10.1267/ahc.36.287
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine-Immune Interactions and Starvation in Mucosal Immunity and Mucosal Inflammation

Abstract: Mutual communication among the immune, neuroendocrine and metabolic systems is essential for the maintenance of gastrointestinal mucosal function. A unique barrier system by the mucosal immune system handles a myriad of infectious and food antigens, while the neuroendocrine system interplays with the immune system in the intestinal mucosa. The close relation between these two systems is associated with the pronounced effects of stress and metabolic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…PTSD is an anxiety disorder for certain severe psychological consequences of exposure to, or confrontation with, stressful events that a person experiences as highly traumatic. It has been reported that stress can lead to changes in the neuroendocrine system, thereby affecting the immune system and metabolic system [ 17 ]. In the neuroendocrine system, the hypothalamic-pituitary-adrenal axis (HPA-axis) is the most important, and glucocorticoid is the next most important factor.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is an anxiety disorder for certain severe psychological consequences of exposure to, or confrontation with, stressful events that a person experiences as highly traumatic. It has been reported that stress can lead to changes in the neuroendocrine system, thereby affecting the immune system and metabolic system [ 17 ]. In the neuroendocrine system, the hypothalamic-pituitary-adrenal axis (HPA-axis) is the most important, and glucocorticoid is the next most important factor.…”
Section: Introductionmentioning
confidence: 99%